Travel bubble: risk anxiety, risk attitude and intention to travel during Covid-19 outbreak / Juliana Langgat ... [et al.] - Langgat, Juliana; Pawan, Marry Tracy; Fabeil, Noor Fzlinda; Pazim, Khairul Hanim (Faculty of Hotel & Tourism Management, Universiti Teknologi MARA, 2021)
The COVID-19 pandemic has made the tourism industry in Malaysia decline drastically. The outbreak has continued for almost two years and has decreased local and international tourist arrivals. The declinations are put under the Movement Control Order (MCO) execution, and safety precautions were issued when travelling around. Nevertheless, the impressive rate of deterioration in pandemic transmission gives a new shade to domestic tourism. The Ministry of Tourism has put forward an initiative that can revitalise the economic sector in the country by introducing the travel bubble destinations among Malaysians. With that, the main purpose of this study is to explore the travel bubble risk anxiety, risk attitude, and intention to travel among Malaysian when COVID-19 is still plaguing the nation. A self-administered survey was conducted online using a snowballing technique. The collected data were keyed and analysed accordingly and answered the objective of the study. The main findings of this study highlighted that those respondents would feel anxious and worried about their safety when participating in the travel bubble. Statistical significance also revealed the respondents' intentions to travel during the COVID-19 outbreak. Further discussions of the findings were also highlighted to deliberate the implications of the study.